MINANGKABAU WOMEN IN THE GRIP OF TRADITION IN THE FILM THE SINKING OF THE VAN DER WIJCK SHIP: Perempuan Minangkabau Dalam Cengkraman Adat Dalam Film Tenggelamnya Kapal Van Der Wijck - Meri Erawati; Liza Husnita; bella agustini (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the representation of Minangkabau women's position in the matrilineal customary system and the forms of resistance that emerge in the film Tenggelamnya Kapal Van Der Wijck. This film shows how women are faced with the dilemma between customary traditions and personal desires, with a focus on the character Hayati. The study uses a qualitative approach with historical methods and critical discourse analysis. The theories used are postcolonial feminist theory and Stuart Hall's theory of representation. The results show that women in Minangkabau customs have a high symbolic position but are practically still controlled by patriarchal structures. The forms of resistance shown are passive and symbolic resistance, showing that women still have agency even within customary limitations. This film is a reflection of social criticism of customary norms that limit women's freedom.